2009
DOI: 10.1007/s12291-009-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR (Ala 222 Val) polymorphism and AMI in patients with type II diabetes mellitus

Abstract: The prevalent Ala222Val single nucleotide polymorphism of the MTHFR gene has been shown to be associated with type II diabetes. The objective of the present study was to find out whether there is genetic predisposition for development of acute myocardial infarction in type II diabetes mellitus among South Indian Tamil population. PCR-based restriction enzyme analysis was performed in DNA isolated from 120 acute myocardial infarction patients with diabetes mellitus and 100 non diabetic healthy individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…This result is consistent with Hermans et al, 2006, Angeline et al, 2009and Sun et al, 2009. A large body of data has showed that the genetic variant (C677T) in the MTHFR gene is associated with peripheral, cerebral and coronary arteries (Ilhan et al, 2007) (Khandanpour et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…This result is consistent with Hermans et al, 2006, Angeline et al, 2009and Sun et al, 2009. A large body of data has showed that the genetic variant (C677T) in the MTHFR gene is associated with peripheral, cerebral and coronary arteries (Ilhan et al, 2007) (Khandanpour et al, 2009).…”
Section: Discussionsupporting
confidence: 77%